TEMPO Derivatives as Alternative Mild Oxidants in Carbon–Carbon Coupling Reactions - García Mancheño, Olga; Stopka, Tobias (Synthesis, 2013)
TEMPO-type oxidants are fundamentally associated with polymer chemistry, radical trapping processes, or the oxidation of alcohols to carbonyl compounds. However, in the past few years new exciting transformations using these kinds of oxidants in the area of C–C and C–heteroatom coupling have emerged. This review focuses on the application of TEMPO and its derivatives as mild reagents or catalysts in oxidative C–C coupling reactions. The review is divided into two main sections: i) the direct coupling of C–H bonds and ii) the use of organometallic reagents such as Grignard or boron species to generate the new C–C bond. In the last section, oxidative C–C/C–O tandem-coupling reactions, in which the TEMPO derivatives are incorporated in the final product, are also briefly described. 1 Introduction2 Oxidative Couplings of C–X Bonds2.1 C–C Bond Couplings of Grignard Reagents2.2 C–C Bond Couplings of Boron Reagents 3 Oxidative Couplings of C–X with C–H Bonds3.1 C–C Bond Couplings with Grignard Reagents3.2 C–C Bond Couplings with Boron Reagents 3.3 Tandem C–C/C–O Coupling Reactions with Olefins 4 Oxidative Couplings of C–H Bonds4.1 C(sp2)–H Bond Functionalizations4.2 C(sp3)–H Bond Functionalizations5 Conclusions
Keywords: TEMPO; oxidations; C–C couplings; C–H functionalizations; synthetic methods